1993
DOI: 10.1148/radiology.189.3.8234706
|View full text |Cite
|
Sign up to set email alerts
|

Refractory ascites: early experience in treatment with transjugular intrahepatic portosystemic shunt.

Abstract: These results are comparable to those for other forms of treatment of ascites. The authors do not, however, recommend TIPS in patients with a Child-Pugh score greater than 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(28 citation statements)
references
References 0 publications
1
25
0
2
Order By: Relevance
“…ascitic fluid accumulation in the pleural space and therefore caused by portal hypertension, TIPS should effectively conThere were six deaths; one patient died of postprocedure sepsis after 7 days and two patients died of sepsis unrelated to trol hepatic hydrothorax. Our group 10 and others 11,12 have reported the successful use of TIPS to control refractory asci-TIPS. There was one death each caused by respiratory failure, liver failure, and hepatocellular carcinoma.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…ascitic fluid accumulation in the pleural space and therefore caused by portal hypertension, TIPS should effectively conThere were six deaths; one patient died of postprocedure sepsis after 7 days and two patients died of sepsis unrelated to trol hepatic hydrothorax. Our group 10 and others 11,12 have reported the successful use of TIPS to control refractory asci-TIPS. There was one death each caused by respiratory failure, liver failure, and hepatocellular carcinoma.…”
Section: Resultsmentioning
confidence: 84%
“…14 This treatment has been associated with several major com-experience of others. 11,21,22 Encephalopathy was the primary complication but was controlled with conservative medical plications including pain, a prolonged intensive care unit stay, 9 and the inability to remove the required chest tube management in each case. In summary, hepatic hydrothorax is an uncommon condibecause of reaccumulation of fluid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] A number of studies have also shown that the reduction in portal pressure induced by TIPS is associated with beneficial effects on renal function and neurohumoral factors in patients with cirrhosis and ascites, including an increase in sodium and water excretion and a reduction in the activity of vasoconstrictor and antinatriuretic systems. [15][16][17][18][19][20][21][22] By contrast, the effects of TIPS in patients with HRS are not well characterized. Several case reports and preliminary data suggest that TIPS may improve renal function in cirrhotic patients with HRS.…”
mentioning
confidence: 99%
“…
Refractory ascites is defined as ascites that cannot beTo date, there are 12 published papers reporting the results of 11 uncontrolled and 1 randomized controlled mobilized, or the early recurrence of which cannot be prevented despite maximal diuretic therapy of 400 mg of studies which assessed the efficacy of TIPS as a treatment for refractory ascites [9][10][11][12][13][14][15][16][17][18][19][20]. The only randomized conspironolactone or 30 mg of amiloride plus up to 120 mg of furosemide daily for at least 1 week despite being on trolled studies compared TIPS versus large volume paracentesis [15].
…”
mentioning
confidence: 99%